Flavor enhancers and/or Vitamin C in growing-finishing rations - Koch, B.A.; Allee, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Supplemental vitamin C fed at two different levels (550 or 1,100mg, per kg, of diet) did not improve animal performance at the swine research center. Adding apple flavor or sodium bicarbonate did not change results.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Flavor enhancers; Vitamin C; Growing-finishing rations